Grammatical analysis of titles The Timi issue is an example (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
Arab grammarians were interested in issues of grammar, and they raised a great deal of controversy around it. Each group of them saw a different vision from the other according to the change in view of the meaning, which is the basis of parsing, and the titled issues are one of the indications of this usual grammatical activity in Arab gatherings and dialogues in general.The Timi issue is one of the issues that preoccupied researchers and scholars in the past, and it revolved around the conditional (if) and the opinions of grammarians about it. This issue is considered one of the issues that talks about tools in Arabic grammar. Grammarians often notice the use of the word tool in subjects with various operators, such as those consisting of nouns, verbs, and letters, such as exclusion operators, or letters and nouns only, such as question and conditional operators, whether the condition is assertive or non-assertive. These tools play a role in giving speech clarity, which is why there has been a lot of discussion about them, and they have been fertile material for Arab grammarians, ancient and modern. They are material that have carved in the history of grammar thresholds for a worthwhile lesson, reflecting the depth of Arabic sentence structure, its accuracy, and the meanings and connotations it establishes.The research chose the taymiyya issue as a field for grammatical analysis, and it is one of the so-called issues. This study focused on the opinions of grammarians about it, and the grammatical principles that emerged in this issue, such as hearing, analogy, assimilation, and so on.